PENGARUH ETIKA BIROKRASI TERHADAP PROFESIONALITAS PELAYANAN PUBLIK DI KANTOR CAMAT MALALAYANG KOTA MANADO - Pai, Faisal Putra; Pangkey, Masje Silija; Tampi, Gustaf Budi (Sam Ratulangi University, 2016)
ABSTRACT : Bureaucracy has ethics that apply to the entire apparatus. Professionalism of publicserviceis a demand that must be realized int he bureaucracy. This study aimsto determine the effectofthe bureaucratic ethic of public service professionalism Malalayang Head Office of Manado City.This study usesquantitative methods. Research was carriedby 40 votes districts Malalayanggovernment apparatus. The data used areprimary data obtained through a questionnaire. The analysistechniq ueused to test the hypothesis is simple statistical regression analysis and simple correlation orkoreasi product moment. The result showed that the direction ofthe regression coefficients andcorrelation coefficientsof the variables bureaucratic ethicof public service professionalism is posifiveand significant atthe 0.01 level of significan ceorconfidence level of 99%.Based onthe results ofthat study concluded that the bureaucratic ethic positive and significantimpacton the professionalism ofthe public service in the sub-district office Malalayang.It is recommended that the understanding, appreciation and practice of ethical apparatusagainst bureaucracy needs to be improved through the development of ethics bureaucracy to theapparatus should be donemore intensively. Application of ethics bureaucracy by bureaucraticapparatus needs to be exemplary of the leaders or elite bureaucracy its elfso that it takesthecommitment of the elite bureaucracy to implement ethics bureaucracy properly.Keywords: ethics bureaucracy, professional services public